Analisis Pengaruh EVA dan ROE Terhadap Harga Saham LQ 45 di Bursa Efek Indonesia Periode 2009 – 2011 - Ananto, Niel (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
Economic value Added (EVA) and Return on Enquity (ROE) are the indicators of company's profitability. EVA figures market value of company and ROE figure its book value. EVA model developed by G. Bennet Stewart. Net Operating Profit After Tax (NOPAT), Invested Capital and cost of Capital are independent variables for EVA while net income and shareholder’s equity are independent variables for ROE. This research attempted to investigate the correlation between EVA and Stock Price of companies included in LQ 45 at The Jakarta Stock Exchange. Pearson Correlation was used to analize the data and samples used in study were 20 companies. This research concluded that EVA and Stock Price had significant correlation while ROE and stock Price had no significant correlation.